As representações dos alunos do gênero masculino no Curso de Pedagogia: homens e identidades na rota de conflitos - MONTEIRO, Gabriel Rocha (2021)
The object of study of this research is part of the complex of tensions experienced by male students in the Pedagogy Course of a university center in the city of Imperatriz- MA. Its problematization is the representations of these students in the daily life of the said course, and the general objective was to analyze the representations of male students in that course. Theoretically, we selected a group of authors who deal with the trajectory of pedagogy to constitute itself as a field of study that investigates the nature and purposes of education. As a category of analysis, a foundation was sought in the Theory of Social Representations by Moscovici (1978, 2001 and 2007), complemented by the works of Sousa (2011) and Jodelet (2001). Methodologically, the principles of qualitative research were adopted and had as informants five male students enrolled in the sixth to eighth periods of the course. Data collection took place through a semi-structured interview. The research made it possible to verify that the social representations associated with the Pedagogy Course are still predominantly female; that male presence is limited to a small number of male students; that in the training process of the course, the greatest difficulties of male students refer to the internship period in Early Childhood Education; between others. It was observed that the biggest conflicts come from the observation that the male teacher is highly rejected in Kindergarten and early elementary schools. Attempts to segregate teachers and children were observed, operated in the form of not leaving the teacher alone with the child.